The Effect of Internal Financial Indicators on the Tendency of Accounting Fraud - Iswati, Dana; Nindito, Marsellisa; Zakaria, Adam (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This research is carried out to prove factors of tendency of accounting fraud in companies empirically. Variable used in predicting the tendency of accounting fraud is profitability level, capital turnover, financial leverage, assets composition, and firm size tendency of accounting fraud. The population is companies registered in Indonesia Stock Exchange that are suspected to fraud the accounting during observation year 2013 – 2015. Samples are taken by using purposive sampling, there are 12 companies are proven to be done fraud accounting and 12 companies are not. Data is analysed by using logistic regression analysis and Hosmer and Lemeshow test to measure the model. The result shows that capital turnover and assets composition has significant influence on tendency of accounting fraud. Besides, profitability, financial leverage, and firm size has insignificant influence on tendency of accounting fraud variable. This research concluded that capital turnover and assets composition can be used as predictor of tendency of accounting fraud in a company.